In vitro anthelmintic activity and in silico analysis of monoterpenes, sesquiterpenes, and semisynthetic derivatives against Eisenia foetida - Andrea Leticia Cáceres, Elvio Gayoso, Rosa Guillen, Nelson Luis Alvarenga (Journal of Applied Pharmaceutical Science, 2024)
Helminthiases remain a worldwide public health problem, mainly in not-developed countries. Available drugs are scarce, and the risk of developing resistance by the parasites is always present. Natural products remain a valid alternative in the search for new antiparasitic drugs. Among them are monoterpenes and sesquiterpenes, standard components of essential oils. This work evaluated the in vitro activity of monoterpenes, sesquiterpenes, and semi-synthetic derivatives against Eisenia foetida using albendazole as a positive control. Gas chromatography coupled with mass spectrometry was used to determine the structure of the derivatives. In silico analysis was also performed on probable molecular targets such as β-tubulin, acetylcholinesterase (AChE), and γ-aminobutyric acid B (GABA B) receptor. The compounds with hydroxyl groups in their structure, such as linalool and (S)-cis-verbenol, showed better biological activity, superior to the reference drug. The binding affinity of these compounds was also found in silico with AChE, GABA B receptor, and β-tubulin. These results demonstrate that natural products may constitute lead compounds for developing new anthelmintic drugs.
Keywords: Anthelmintics, monoterpenes, sesquiterpenes, in silico, Eisenia foetida